Preparation of Mixed Nano Metal Composites for Nuclear Radiation Shielding Applications - Harish V, Pavan N, S Chandramma (International Journal of Advanced Science and Technology, 2020)
Rapid Developments in nuclear technology and radiation shielding in the last century have standard composites to the use of radiation in different areasof human activity. These are not just the energetics but also food, agriculture, medicine, industry and science.Thus, radiation has become an inevitable phenomenon in our lives. Since we cannot isolate radiation from ourlife, the radiation protection methods should be available. As alternatives to conventional radiation preventionmethods, such as lead and heavy concrete shielding, more functional materials need to become the focus of research.The development of the least harmful to the environment, easily applicable, flexible radiation shields has becomevery important. In this research study,nano mixed metal composites likelead oxide (PbO), bismuth oxide (Bi2O3), tungsten oxide (WO3) withpolymer matrix composite panels, doped with different ratios of mixed powder, were produced and characterized by scanning electron microscopy (SEM). Gamma and neutronradiation shielding properties of these materials were investigated and also observed intensity at 2-theta level.Scanning electron microscopy were used to characterize the progress of mixed metal compositesmetal particles morphology through the standard process and to ensure the nanometric size of the size nano-composites then mixed with polymer matrix for gamma ray attenuation. The results have been compared with the leadas the standard shielding material.